The Influence Of Return On Equity (Roe), Return On Assets (Roa) And Net Profit Margin (Npm) On PT Minimal Tiga Kata, 2019 – 2023 - J. Hartanto, Andy (Yayasan Gema Bina Nusantara, 2023)
This study aims to determine the effect of Return On Equity (X1), Return On Assets (X2), and Net Profit Margin (X3) on Stock Prices (Y) at Minimum Three Word PT in 2019-2023. The population in this study is the financial statements of PT Minimum Three Words and a sample of 17 samples in quarterly form from 2019 – 2023. Based on the results of the multiple linear regression test, the regression equation is Y=2250.470+4.349X_1-68.117X_2+208.031X_3+e. Based on the results of the partial test, it was found that the variable Return On Equity did not have a significant effect on stock prices, Return On Assets had a significant effect on stock prices, while Net Profit Margin had a significant effect on stock prices. The results of simultaneous testing show that Return On Equity, Return On Assets, and Net Profit Margin have a significant effect on stock prices. The R Square value in this study is 0.384 or 38.4%, namely the contribution of the variables ROA, ROE and NPM to stock prices while the remaining 61.6% is influenced by factors other than ROA, ROE and NPM. Keywords: Return On Equity, Return On Assets, Net Profit Margin, Stock Prices